Pharmaceutical Agents for Targeting Autophagy and Their Applications in Clinics - Ulash Kench; Susanna Sologova; Elena Smolyarchuk; Vladimir Prassolov; Pavel Spirin (Pharmaceuticals, 2024)
Autophagy is the process by which damaged regions of the cytoplasm and intracellular pathogens are degraded. This mechanism often serves an adaptive role in cells, enhancing their survival. It plays a direct or indirect role in the development of various pathological conditions within the body. This phenomenon is common in various malignant diseases, where autophagy is associated with the resistance of transformed cells to chemotherapy. Conversely, abnormal activation of autophagy can trigger cell death, a process often seen in neurodegenerative conditions. Given that dysregulation of autophagy is associated with the progression of numerous pathological conditions, this is of significant interest to the developers of drugs that can effectively modulate autophagy for both basic research and clinical applications. Here, we provide a brief description of the mechanism of macroautophagy, the most prevalent form of autophagy identified in humans. We also discuss the clinical potential of drugs that can modulate autophagy, highlighting their use in combating diseases associated with direct or indirect dysregulation of this essential process.